Two novel binuclear sulfonic-functionalized ionic liquids: Influence of anion and carbon-spacer on catalytic efficiency for one-pot synthesis of bis(indolyl)methanes - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie; Juan, Joon Ching (Elsevier, 2018)
Two new binuclear sulfonic-functionalized ionic liquids with four-carbon spacer were synthesized and their structures were characterized by FTIR, MS, 1H and 13C NMR; then some physical properties and pH of the aqueous solution of new task-specific ionic liquids were determined. Their dual solvent-catalytic activity were studied for the synthesis of bis(indolyl)methanes under mild conditions. The catalytic activity of these ionic liquids were compared with some ionic liquids derived from pyrazinium, piperazinium, benzimidazolium, imidazolium mono- or di-cation containing chloride and hydrogen sulfate as counter anion under optimized conditions. It was proved that the new ionic liquids containing two sulfonic imidazole moieties with four-carbon spacer as well as hydrogen sulfate as acidic counter anion were superior to the previously reported ionic liquids.